2010
DOI: 10.1007/s11947-010-0416-3
|View full text |Cite
|
Sign up to set email alerts
|

Separation of Iron-Binding Peptides from Shrimp Processing By-products Hydrolysates

Abstract: Separation of iron-binding peptides derived from shrimp processing by-products (SPB) by Alacase hydrolysis was investigated. The highest iron-binding capacity of the hydrolysate (17.5 μmol/g of protein) was obtained with Alacase at a degree of hydrolysis of 8%. The molecular weight (MW) distribution on gel permeation chromatography (GPC) showed that it was ranging from 1 to 6 kDa. By separating with ion-exchange chromatography on SPSepharose Fast Flow and gel filtration on Sephadex G-25, one fraction with high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(47 citation statements)
references
References 45 publications
3
39
0
2
Order By: Relevance
“…Lee and Song (2009) isolated an iron-binding nona-peptide, Asp-Leu-Gly-GluGln-Tyr-Phe-Lys-Gly, molecular weight of 1055 Da, from porcine blood plasma protein hydrolysate with Flavourzyme. Huang et al (2012) obtained a hepta-peptide (699 Da) with iron-binding ability from shrimp processing byproducts hydrolysate.…”
Section: Results and Discussion Molecular Weight Distribution Of The mentioning
confidence: 99%
“…Lee and Song (2009) isolated an iron-binding nona-peptide, Asp-Leu-Gly-GluGln-Tyr-Phe-Lys-Gly, molecular weight of 1055 Da, from porcine blood plasma protein hydrolysate with Flavourzyme. Huang et al (2012) obtained a hepta-peptide (699 Da) with iron-binding ability from shrimp processing byproducts hydrolysate.…”
Section: Results and Discussion Molecular Weight Distribution Of The mentioning
confidence: 99%
“…With enzymatic hydrolysis, more and more small peptides produced. But many reports showed that the iron or ferrous binding ability of peptides did not show positive or negative relationship with molecular weight of peptides (Wu et al, 2012;Huang et al, 2011;Kim et al, 2014). Therefore, high FAB hydrolysis time might be one of any points during whole hydrolysis process.…”
Section: Effects Of Hydrolysis Time and Enzyme Additive Amountmentioning
confidence: 98%
“…Hence, iron fertilization in food is an effective defending method for iron deficiency. In order to uptake iron absorption rate, there have been many studies about non-heme iron binding bioactive peptides in recent years (Lee and Song, 2009;Huang et al, 2011;Torres-Fuentes et al, 2012;Kim et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…특히 단백 질에 비해 크기가 작은 생리 활성 펩타이드는 생체내로 쉽게 흡수 될 수 있으며, 다양한 기능적 특성을 갖는다 [10]. 생리활성 팹타이드의 효과로는 미네랄운송 [11,12], 항고혈압 [13], 항균활성 [14] …”
Section: 서론unclassified